2018
DOI: 10.1111/bcpt.12950
|View full text |Cite
|
Sign up to set email alerts
|

The Cumulative Daily Tolerance Levels of Potentially Toxic Excipients Ethanol and Propylene Glycol Are Commonly Exceeded in Neonates and Infants

Abstract: Polymedicated neonates and young infants may be at risk of harmful cumulative exposure to toxic excipients like ethanol, propylene glycol and benzyl alcohol during routine clinical care. The aim of this study was to calculate the cumulative daily alcohol exposure (mg/kg/day) in polymedicated neonates and infants and compare these levels to the tolerance limits found in guidelines published by European Medicines Agency (EMA). As part of the SEEN study, all medicinal products administered to neonates and infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
0
22
0
2
Order By: Relevance
“…Further observations revealed that excipient amounts exceeded the recommendations for maximum daily intake for adults in 19% of oral medicines. Additionally, a Danish study showed that the exposure of benzyl alcohol, ethanol and propylene glycol in hospitalized neonates and infants less than 2 years of age was substantial and the cumulative daily exposure frequently exceeded the tolerance limits stated by EMA [14].…”
Section: Introductionmentioning
confidence: 99%
“…Further observations revealed that excipient amounts exceeded the recommendations for maximum daily intake for adults in 19% of oral medicines. Additionally, a Danish study showed that the exposure of benzyl alcohol, ethanol and propylene glycol in hospitalized neonates and infants less than 2 years of age was substantial and the cumulative daily exposure frequently exceeded the tolerance limits stated by EMA [14].…”
Section: Introductionmentioning
confidence: 99%
“…The dose size of EFV is 200 mg for pediatric patients and 600 mg for adults and as a nanoemulsion the dose unit is relatively small and is not expected to produce blood ethanol levels above regulated limits [ 38 ]. The European Medicines Agency (EMA) recommends a daily limit of 260.5 mg/kg/day of ethanol [ 39 ]. The levels for Span ® 20 (A), Tween ® 80 (B) and ethanol (C) used in the mixture fell in the range between the minimum and maximum levels listed in Table 2 with the sum of the components A, B and C always totaling 100%.…”
Section: Methodsmentioning
confidence: 99%
“…The participants in this study believed that, in case the printing method used does not enable printing of a QR code, other measures should be taken to ensure identification of the drug product and, thus, to prevent medication errors. In drug development of pediatric medicines, one must consider that the colorant as well as other excipients are safe for use in children, since investigations have shown that neonates and infants are extensively exposed to harmful excipients during oral administration of medicines [38][39][40]. Furthermore, this study shows that healthcare professionals prefer dosage forms containing excipients that enable the administration of the dosage form through enteral feeding tubes as well as after dissolving or dispersing the dosage form in liquid, e.g., water.…”
Section: Main Findingsmentioning
confidence: 99%